Front Cover: A high‐throughput all‐optical laser‐scanning imaging flow cytometer with biomolecular specificity and subcellular resolution (J. Biophotonics 2/2018). Issue 2 (8th February 2018) - Yan, Wenwei; Wu, Jianglai; Wong, Kenneth K. Y.; Tsia, Kevin K.
Abstract : A new type of high‐throughput imaging flow cytometer (>20 000 cells s ‐1 ) based upon an all‐optical ultrafast laser‐scanning imaging technique, called free‐space angular‐chirp‐enhanced delay (FACED) is reported. FACED imaging flow cytometers enables high‐throughput visualization of functional morphology of individual cells with subcellular resolution. It critically empowers largescale and deep characterization of single cells and their heterogeneity with high statistical power— an ability to become increasingly critical in single‐cell analysis adopted in a wide range of biomedical and life‐science applications. Further details can be found in the article by Wenwei Yan et al. (e201700178 ) Abstract : A new type of high‐throughput imaging flow cytometer (>20 000 cells s ‐1 ) based upon an all‐optical ultrafast laser‐scanning imaging technique, called free‐space angular‐chirp‐enhanced delay (FACED) is reported. FACED imaging flow cytometers enables high‐throughput visualization of functional morphology of individual cells with subcellular resolution. It critically empowers largescale and deep characterization of single cells and their heterogeneity with high statistical power— an ability to become increasingly critical in single‐cell analysis adopted in a wide range of biomedical and life‐science applications. Further details can be found in the article by Wenwei Yan et al. (e201700178 )